2011
DOI: 10.1121/1.3544490
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of asymmetric glottal jet deflection during phonation

Abstract: Two-dimensional numerical simulations are used to explore the mechanism for asymmetric deflection of the glottal jet during phonation. The model employs the full Navier-Stokes equations for the flow but a simple laryngeal geometry and vocal-fold motion. The study focuses on the effect of Reynolds number and glottal opening angle with a particular emphasis on examining the importance of the so-called "Coanda effect" in jet deflection. The study indicates that the glottal opening angle has no substantial effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 26 publications
7
43
1
Order By: Relevance
“…Thus, although the vortex structures and jet evolution observed in the current model is seemingly different from that observed in the 2D model (Zheng et al, 2011a), the mechanism for the jet deflection is consistent with that identified in the 2D model in that it is dominated by the downstream vortex dynamics. This conclusion is also consistent with the very recent work of Mattheus and Br€ ucker (2011) which investigated the differences of asymmetric jet deflection in 2D and 3D models.…”
Section: B Glottal Jet Evolutionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, although the vortex structures and jet evolution observed in the current model is seemingly different from that observed in the 2D model (Zheng et al, 2011a), the mechanism for the jet deflection is consistent with that identified in the 2D model in that it is dominated by the downstream vortex dynamics. This conclusion is also consistent with the very recent work of Mattheus and Br€ ucker (2011) which investigated the differences of asymmetric jet deflection in 2D and 3D models.…”
Section: B Glottal Jet Evolutionsupporting
confidence: 77%
“…Characteristic features of phonation, including glottal jet evolution, waviness in glottal jet, mucosal wave type VF vibration and 1:1 entrainment of principal modes of vibrations have been discussed in detail. The evolution pattern of glottal jet provides support to the notion that (Zheng et al, 2011a;Mattheus and Br€ ucker, 2011) the glottal flow asymmetry is driven primarily by the postglottal vortex dynamics.…”
Section: Discussionmentioning
confidence: 52%
“…The flow was assumed to separate from the glottal wall at a point downstream of the minimum glottal constriction at which the glottal width was 1.2 times the minimum glottal width. Note that the flow separation model of this study gives only a rough estimation (Sidlof et al, 2011) of the complex flow separation pattern in asymmetric vocal fold vibration (see e.g., Zheng et al, 2011). It was chosen in this study because of its simplicity and low computational costs, which makes it possible to perform the parametric study as reported in the following text.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In a recent study Zheng et al 2 investigated the jet deflection by a 2D numerical simulation of the glottal constriction in the case of constant glottal opening angle. They state that the large scale asymmetry of the flow downstream of the constriction is mainly influencing the jet deflection.…”
Section: Introductionmentioning
confidence: 99%